2007
DOI: 10.3846/13928619.2007.9637811
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Dynamic Soil‐structure Interaction Analysis of Buildings

Abstract: The objective of this research is to evaluate the effects of soil‐structure interaction (SSI) on the modal characteristics and on the dynamic response of structures. The stress had an impact on the overall behaviour of five storeys reinforced concrete (R/C) buildings typically encountered in Algeria. Sensitivity studies are undertaken in order to study the effects of frequency content of the input motion, frequency of the soil structure system, rigidity and depth of the soil layer on the dynamic response of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The numerical methods of direct approach like finite element method (FEM), spectral element method (SEM) and boundary element method (BEM) is currently used methods for SSI analysis. Hessam et al and Gouasmia et al showed the importance of considering nonlinear SSI effects in finite element (FE) approach of SSI [8,9]. Omar et al showed FE method for better response than experimental methods and the numerical methods are best suitable for dynamic problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical methods of direct approach like finite element method (FEM), spectral element method (SEM) and boundary element method (BEM) is currently used methods for SSI analysis. Hessam et al and Gouasmia et al showed the importance of considering nonlinear SSI effects in finite element (FE) approach of SSI [8,9]. Omar et al showed FE method for better response than experimental methods and the numerical methods are best suitable for dynamic problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…It will change free-field ground motion. Studies on soil-structure interaction were conducted by several researchers [21][22][23][24][25][26][27]. Ivanovic [23] performed 3D finite element analysis of a seven-story reinforced concrete building supported by the piled foundation on loose soil.…”
Section: Case Study (Sungur Bey Mosque)mentioning
confidence: 99%
“…A set of factors depending on the structural abrasion of masonry foundations were proposed utilizing 2D FEM models [26]. Gouasmia et al [27] developed analytical models of a 5 story reinforced concrete building to investigate soil-structure interaction. Allowing the structure to slide or uplift has not changed on measured acceleration or displacement whereas the base shear and overturning moments reduced 74%.…”
Section: Case Study (Sungur Bey Mosque)mentioning
confidence: 99%
“…One of the most important aspects of structural analysis is soil-structure interaction (SSI). Such interaction may alter the dynamic characteristics of structures and consequently may be beneficial or detrimental to the performance of structures (Gouasmia, Djeghaba 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The main idea behind this investigation is motivated by the fact that there is still great uncertainty as to the significance of seismic soil-structure interaction (SSI) for ordinary structures typically encountered in Algeria (Gouasmia, Djeghaba 2005). There may be both beneficial and adverse effects of SSI.…”
Section: Introductionmentioning
confidence: 99%